2017
DOI: 10.1002/nau.23321
|View full text |Cite
|
Sign up to set email alerts
|

Effects of pedunculopontine nucleus stimulation on human bladder function

Abstract: Bilateral PPN DBS did not have a detrimental effect on urodynamic filling parameters or produce detrusor overactivity, but did slightly increase maximal capacity. Possible mechanisms include long-range connectivity or local effects at the pontine micturition center.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 25 publications
0
10
1
Order By: Relevance
“…Another study by Winge K (2012) revealed that nocturia was significantly improved after DBS, which differed from our study 20. The study by Roy HA (2018) found that DBS did slightly increase maximal capacity, and the study by Mock S (2016) revealed that there were notable improvements in QOL for LUTS post-DBS in the subthalamic nucleus target 21,22. Overall, the number of patients included in these studies was limited, and most of the research focused more on clinical results.…”
Section: Discussioncontrasting
confidence: 80%
“…Another study by Winge K (2012) revealed that nocturia was significantly improved after DBS, which differed from our study 20. The study by Roy HA (2018) found that DBS did slightly increase maximal capacity, and the study by Mock S (2016) revealed that there were notable improvements in QOL for LUTS post-DBS in the subthalamic nucleus target 21,22. Overall, the number of patients included in these studies was limited, and most of the research focused more on clinical results.…”
Section: Discussioncontrasting
confidence: 80%
“…Urge incontinence attributed to stimulation of the pontine micturition centre was described in one patient (Aviles-Olmos et al, 2011). Further investigation into this phenomenon with urodynamic testing found no detrimental effects on urodynamic filling parameters and detrusor activity but a slight increase in maximal bladder capacity (Roy et al, 2017).…”
Section: Ppn-dbs Study Results In Humans: Side Effects and Non-motor mentioning
confidence: 91%
“…Important areas identified by this approach included the frontal lobes in general (Maurice-Williams, 1974), and brainstem regions including the PAG (Yaguchi et al, 2004). More recently, alterations in bladder function have been reported following implantation of DBS electrodes within the thalamus (Kessler et al, 2008), subthalamic nucleus (STN; Seif et al, 2004; Herzog et al, 2006, 2008), internal globus pallidus (GPi) (Mordasini et al, 2014), PAG (Green et al, 2012) and pedunculopontine nucleus (PPN; Aviles-Olmos et al, 2011; Roy et al, 2018b), implicating all of these regions in some aspect of human urinary control. Finally, developments in functional brain imaging have facilitated a controlled, systematic, experimental whole-brain approach to investigate the neural control of the bladder in both healthy human subjects and those with bladder disorders.…”
Section: Supraspinal Organization Of Bladder Conrol and Overlap With mentioning
confidence: 99%